Memória da produção em design gráfico na cidade de Bauru: (1987 a 1990) - Valderramas, Renato [UNESP] (2014)
The objective of this study is to promote and rescue the memory of Traço Magazine, organized and edited by a group of graphic artistic, also called Traço, located in the city of Bauru from 1987 to 1990. The research is justified by the low number of publications that has the objective of studying the Brazilian graphic design with a focus on regionalized productions, as well the importance of preserving the cultural heritage, in which that the maganize is part of and, finally, the establishment of a panorama that enable our understanding of the birth and establishment of the graphic design market in the region of Bauru. The present survey observed the terminology employed in the professional industry, especially in specific activities such as the graphic deisgn field, with the purpose of establishing minimum parameters for their understanding and use. It also addressed the discussion about what Graphic Design is, which is considered as a parameter the definitions of national authors, due to the fact that these authors have a recognition of their relevant activity and action, and closer to the Brazilian reality. It was also observed the Brazilian editorial market in the 1980s, discussing publications considered outstanding in terms of editorial design. Finally, a detailed presentation of Traço Group and Traço Magazine was made from information gathered both by the periodic itself as from interviews held with most of the group members. This investigation, with an exploratory qualitative approach and a documentary bibliographic imprint, relies on the application of techniques related to literature review and field research along with semi-structured interviews that were conducted with most of the members from the group that were responsible for the maganize publication. Furthermore, the collecion and analysis of all figures relating to issues of Trace Magazine (1,2,3,4 and Special Editon), which were considered in editorial and graphic...